COP17 Climate-smart agriculture trailer - ARDD 2011 - International Center for Tropical Agriculture (2011)
Why is climate-smart agriculture important, and can it work? Watch this 3 minute trailer for an insight into what the challenges are, and where the solutions might lie. Originally produced to introduce the Learning Events section of Agriculture and Rural Development Day at the United Nations COP17 climate change conference in Durban, South Africa, Dec 2011. Find out more about the CGIAR's Climate Change, Agriculture and Food Security research program: www.ccafs.cgiar.org